Rhizospheric Bacillus isolates control Fusarium wilt on cotton and enhance plant biomass and root development - Aslam, Seema; Baber, Muhammad; Naqqash, Tahir; Javed, Muhammad; Bredenbruch, Sandra; Grundler, Florian M. W.; Schleker, A. Sylvia S. (Frontiers in Microbiology, 2025)
Cotton is a globally significant crop, serving as a source of natural fiber for the textile industry and contributing to various other products. Its economic importance is substantial, impacting livelihoods and international trade. However, cotton production faces numerous challenges, including Fusarium wilt caused by Fusarium oxysporum f. sp. vasinfectum (Fov), which can lead to significant yield and fiber quality losses. Plants alter their root exudate profiles in response to pathogens, often selectively enriching for beneficial rhizobacteria with antagonistic activity and plant growth-promoting traits. This study thus aims to characterize bacteria isolated from the rhizosphere of diseased cotton plants. The antifungal activity of 43 isolates was assessed against Fov in vitro. Eight of these inhibited Fov growth by 68.4 to 76.9%. 16S rRNA sequencing confirmed these isolates as Bacillus species. These eight Bacillus strains were further examined for their different modes of action in vitro, and their effect on cotton plants in greenhouse experiments challenged with Fov. All eight strains produced chitinases and pectinases, seven demonstrated cellulase and three protease activity, six produced urease, and five siderophores. Only B. subtilis SC11 exhibited phosphate solubilization activity. Seed treatments revealed that B. subtilis SC10 and B. subtilis SC11 were the standout treatments reducing Fov-caused symptoms by ~83% compared to Fov-inoculated control plants and most significantly improved plant growth and antioxidant activity. In detail, B. subtilis SC11 increased shoot and root dry weight by 160 and 250%, respectively. B. subtilis SC10 increased peroxidase activity by ~143% and ascorbate peroxidase activity by ~60%, while in B. subtilis SC11 treated plants superoxide dismutase activity increased by ~100%. Bacillus treatments effectively mitigated lipid peroxidation, achieving up to 91.4% reduction (B. subtilis SC10, B. halotolerans SC15), and decreased H₂O₂ accumulation by up to 58.4% (B. halotolerans SC32) compared to the Fov control. Principle component analysis revealed that regarding plant growth parameters, the treatments, and controls were distributed differentially across PC1 and PC2, with 60.30 and 15.62% data variance, respectively, showing the effectiveness of Bacillus isolates in greenhouse experiments. The findings of this study will contribute to the development of sustainable biocontrol strategies for managing Fusarium wilt in cotton.